Effect Dietary Garlic Processed on Performance and Intestinal of Broilers: Pengaruh Pemberian Bawang Putih Olahan pada Performa dan Saluran Pencernaan Broiler - Ariyani Tanti; Yuli Retnani; Iman Rahayu Hidayati Soesanto (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to determine the effect of dietary processed garlic in feed on the performance, intestinal weight, intestinal length, and morphology of the intestinal villi of broilers. A total of 200 Day-Old-Chick (DOC) Cobb strains (unsexed) with an average body weight of 42 ± 3 g were randomly allocated to four experimental groups with five replications, each containing ten chicks per replication. The treatments were T0 (basal diet as control), T1 (basal diet + 3% garlic paste), T2 (basal diet + 3% garlic powder), and T3 (basal feed + 3% black garlic powder). The variables measured were feed intake, body weight gain, feed conversion ratio, final body weight, intestinal weight, intestinal length, and intestinal villi morphology. The data were analyzed for variance based on a Completely Randomized Design. If there was a difference, Duncan's multiple range test was applied. The results showed that the treatment had a significant effect (p<0.05) on intestinal weight, but there was no significant effect on intestinal length and performance. The addition of processed garlic increased the height and width of the villi of the intestines of broilers. The present study's findings suggest that the dietary intake of processed garlic significantly improved the intestinal weight and morphology of broiler villi. However, it did not significantly improve performance. Key words: broilers, garlic processed, intestinal, morphology of villi, supplementation